Usage of PEN as self-vetoing structural material in the LEGEND experiment. (1st March 2022) - Manzanillas, L.; Efremenko, Y.; Febbraro, M.; Fischer, F.; Corominas, M.G.; Hackett, B.; Hayward, C.; Hodák, R.; Majorovits, B.; Muenstermann, D.; Pohl, M.; Rouhana, R.; et al.
Abstract: Polyethylene naphthalate (PEN) is an industrial plastic which is interesting to the physics community as a wavelength-shifting scintillator. Recently, PEN structures with excellent radiopurity have been successfully produced using injection compression molding technology. This opens the possibility for the usage of optically active structural components with wavelength shifting capabilities in low-background experiments. Thus, PEN holders will be used to mount the germanium detectors in the LEGEND-200 experiment. In this contribution the ongoing R&D on PEN is outlined with a focus on the evaluation of its optical properties. In addition, the ongoing efforts for further application of PEN in the LEGEND-1000 experiment are presented.